2009
DOI: 10.1016/j.cell.2009.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Recombination and Replication in DNA Repair of Heavily Irradiated Deinococcus radiodurans

Abstract: Deinococcus radiodurans' extreme resistance to ionizing radiation, desiccation, and DNA-damaging chemicals involves a robust DNA repair that reassembles its shattered genome. The repair process requires diploidy and commences with an extensive exonucleolytic erosion of DNA fragments. Liberated single-stranded overhangs prime strand elongation on overlapping fragments and the elongated complementary strands reestablish chromosomal contiguity by annealing. We explored the interdependence of the DNA recombination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
223
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(235 citation statements)
references
References 41 publications
10
223
0
2
Order By: Relevance
“…First, we have found that DrSSB accumulates in cells during the initial phase of genome reconstruction. It is possible that the increase in DrSSB levels is required to preserve newly generated ssDNA ends for their use as primers in ESDSA (13,46). DNA damage-dependent DrSSB accumulation was also corroborated in a recently published study (42).…”
Section: Discussionmentioning
confidence: 61%
“…First, we have found that DrSSB accumulates in cells during the initial phase of genome reconstruction. It is possible that the increase in DrSSB levels is required to preserve newly generated ssDNA ends for their use as primers in ESDSA (13,46). DNA damage-dependent DrSSB accumulation was also corroborated in a recently published study (42).…”
Section: Discussionmentioning
confidence: 61%
“…Ce n'est pas surprenant : ce sont des protéines qui réparent l'ADN, et pas l'inverse. La démonstration en est apportée chez les bactéries [12,13] et chez les animaux [9] les plus résistants aux radiations : la réparation spectaculaire de l'ADN morcelé par des niveaux extrêmes de radiations ionisantes est due à la protection des protéines contre les dégâts oxydatifs radio-induits et non pas à l'évolution des systèmes nouveaux de réparation [13]. Il semble que les auteurs de cet effet protecteur soient de petites molécules qui neutralisent tous les ROS.…”
Section: Biologie De La Robustesse Et Santé Humaineunclassified
“…Beside manganese accumulation and specific protein protection, survival depends on the efficient and rapid reconstitution of a functional genome from numerous DNA fragments. Recombinational repair with extensive DNA synthesis is used (Slade et al, 2009). DNA repair is primed by recombination proteins RecA and RadA, while the elongation step is performed by Pol III and PolI.…”
Section: Replication and Recombination In A Radiation-resistant Organismmentioning
confidence: 99%